Mechanisms behind surface modification of polypropylene film using an atmospheric-pressure plasma jet. (27th October 2016) - Shaw, David; West, Andrew; Bredin, Jerome; Wagenaars, Erik
Abstract: Plasma treatments are common for increasing the surface energy of plastics, such as polypropylene (PP), to create improved adhesive properties. Despite the significant differences in plasma sources and plasma properties used, similar effects on the plastic film can be achieved, suggesting a common dominant plasma constituent and underpinning mechanism. However, many details of this process are still unknown. Here we present a study into the mechanisms underpinning surface energy increase of PP using atmospheric-pressure plasmas. For this we use the effluent of an atmospheric-pressure plasma jet (APPJ) since, unlike most plasma sources used for these treatments, there is no direct contact between the plasma and the PP surface; the APPJ provides a neutral, radical-rich environment without charged particles and electric fields impinging on the PP surface. The APPJ is a RF-driven plasma operating in helium gas with small admixtures of O2 (0–1%), where the effluent propagates through open air towards the PP surface. Despite the lack of charged particles and electric fields on the PP surface, measurements of contact angle show a decrease from 93.9° to 70.1° in 1.4 s and to 35° in 120 s, corresponding to a rapid increase in surface energy from 36.4 mN m −1 to 66.5 mN m −1 in the short time of 1.4 s. These treatment effects are very similar to what is found in other devices, highlighting the importance of neutral radicals produced by the plasma. Furthermore, we find an optimum percentage of oxygen of 0.5% within the helium input gas, and a decrease of the treatment effect with distance between the APPJ and the PP surface. These observed effects are linked to two-photon absorption laser-induced fluorescence spectroscopy (TALIF) measurements of atomic oxygen density within the APPJ effluent which show similar trends, implying the importance of this radical in the surface treatment of PP. Analysis of the surface reveals a two stage mechanism for the production of polar bonds on the surface of the polymer: a fast reaction producing carboxylic acid, or a similar ketone, followed by a slower reaction that includes nitrogen from the atmosphere on the surface, producing amides from the ketones.